1976
DOI: 10.1073/pnas.73.5.1655
|View full text |Cite
|
Sign up to set email alerts
|

Resting state in normal and simian virus 40 transformed Chinese hamster lung cells.

Abstract: Normal cells deprived of amino acids or serum factors enter a resting state, whereas cells transformed by wild-type simian virus 40 do not. The ability to enter a resting state is temperature-sensitive (ts) in cells transformed by a tsA mutant of simian virus 40. We show further: (i) that when complete medium is added to resting cells, the length of time until the onset of DNA synthesis often exceeds the length of GI in growing cells; (ii) that the length of this interval depends upon the conditions used to ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 18 publications
(8 reference statements)
1
31
0
1
Order By: Relevance
“…Arrests produced by cdc28 or cdc24 mutations or a-factor block belong to the second type. The type 1 arrest appears to be similar to the state of cells previously designated as Go or the resting state in cultured mammalian and avian cells (1,19,25,40). Using cultured human fibroblasts, Augenlicht and Baserga (1) have found that a lag before the onset of DNA synthesis elongated when cells that had been arrested for longer periods were stimulated.…”
Section: Two Types Of G Arrestsmentioning
confidence: 95%
See 2 more Smart Citations
“…Arrests produced by cdc28 or cdc24 mutations or a-factor block belong to the second type. The type 1 arrest appears to be similar to the state of cells previously designated as Go or the resting state in cultured mammalian and avian cells (1,19,25,40). Using cultured human fibroblasts, Augenlicht and Baserga (1) have found that a lag before the onset of DNA synthesis elongated when cells that had been arrested for longer periods were stimulated.…”
Section: Two Types Of G Arrestsmentioning
confidence: 95%
“…A distinctive property of cultured cells existing in Go may be an unusually long delay between the shift of the culture from nonpermissive to permissive conditions for growth and the initiation of DNA synthesis (1,25). Recently, we observed that lymphocytes that had divided recently responded quickly to a stimulus, but lost this ability and became cells that responded slowly when incubated in the absence of the stimulus (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of R point control is accentuated by studies of cells transformed to tumorigenicity by DNA tumor viruses (8)(9)(10). Whereas nontumorigenic cells become quiescent within one generation after the serum concentration is reduced, these transformed cells have lost their growth control and grow in media containing very low concentrations of serum.…”
Section: Introductionmentioning
confidence: 99%
“…Simian virus 40 (SV40), a DNA tumor virus, transforms nonpermissive cells and produces cell lines, transformants, which, unlike cells transformed by RNA tumor viruses (10,23,28), are often deficient in their ability to enter the resting state, or stationary phase, at high cell density (5,10,25,29,30). SV40 transformation has been used to study differentiated functions (for a recent review, see reference 50) and to isolate functional cell lines in culture (3, 6-8, 40, 45, 46).…”
mentioning
confidence: 99%